1982
DOI: 10.1159/000260618
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fluorosis and Localized Enamel Opacities in Fluoride and Nonfluoride Danish Communities

Abstract: Assessment of dental fluorosis and localized enamel opacities was performed amongst children resident in areas having < 0.2, 1.0 and 2.4 parts/106 F- in the drinking water. Evaluation of dental fluorosis was done by Dean’s classification system as well as the clinicohistological system described by Thylstrup and Fejerskov in 1978. Fci was 0.02, 0.56 and 1.33 respectively, and the pattern of dental fluorosis within the dentition followed that previously described for high fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…The TFI has been shown to be more sensitive than the classical Dean index of dental fluorosis when applied to more se vere degrees of dental fluorosis [Thylstrup and Fejerskov, 1978]. In a recent study Wenzel and Thylstrup [1982] have shown a good agreement between scores of indi vidual teeth when using the TFI versus the criteria for dental fluorosis described by Dean [1942], when applied to individuals living in 1-to 2.5-ppm water fluoride areas in Denmark. However, these authors con cluded that the detailed surface classifica tion system based on known histological changes in the tissues (TFI) would permit a better understanding of the dose-re sponse relationship between fluoride in gestion and dental fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…The TFI has been shown to be more sensitive than the classical Dean index of dental fluorosis when applied to more se vere degrees of dental fluorosis [Thylstrup and Fejerskov, 1978]. In a recent study Wenzel and Thylstrup [1982] have shown a good agreement between scores of indi vidual teeth when using the TFI versus the criteria for dental fluorosis described by Dean [1942], when applied to individuals living in 1-to 2.5-ppm water fluoride areas in Denmark. However, these authors con cluded that the detailed surface classifica tion system based on known histological changes in the tissues (TFI) would permit a better understanding of the dose-re sponse relationship between fluoride in gestion and dental fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies reported to date have focused on enamel defects that were associated with systemic factors [Al-Alousi et al, 1975;Wenzel and Thylstrup, 1982;Suckling et al, 1985;Ellwood and O'Mullane, 1995;Lai et al, 1997;Rugg-Gunn et al, 1997;Seow, 1997].…”
mentioning
confidence: 99%
“…It is possible that some teeth we scored as having questionable, very mild, or mild fluorosis in fact were af fected by idiopathic enamel opacities. Some investigators have described diffi culties in differentiating among mild flu orosis, questionable fluorosis, and idi opathic enamel opacities [ Wenzel and Thylstrup, 1982], The relatively high pre valence of fluorosis in children with in complete data was probably due to the use of other fluoride-containing products.…”
Section: Discussionmentioning
confidence: 99%